Pengaruh Penerapan Prinsip Itikad Baik dalam Perjanjian Asuransi terhadap Risiko Penolakan Klaim Berdasarkan UU No. 40 Tahun 2014 - Lira Sepira; Shintia Dwi Lestari; Radit Pranata; Surahman Illahi; Holijah . (CV. ITTC INDONESIA, 2026)
This study examines the application of the principle of good faith in insurance contracts and its impact on the risk of claim rejections under Law Number 40 of 2014 concerning Insurance. The main problem in this study is the continued frequency of claim rejections, triggered by a lack of information transparency and understanding of the policy's contents. This study aims to analyze the application of the principle of good faith, identify the factors causing claim rejections, and examine the legal protection provided to customers. The research method used is normative juridical with a statutory approach and a case study of Bank Indonesia. Data was obtained through literature review and qualitative analysis. The results indicate that the application of the principle of good faith is suboptimal, as indicated by the persistence of dishonesty in conveying information, a lack of understanding of policy clauses, and weaknesses in regulatory implementation. This significantly increases the risk of claim rejections. Therefore, increased transparency, customer education, and more effective oversight are needed to create a fair and trustworthy insurance system.